2021
DOI: 10.14202/vetworld.2021.2332-2338
|View full text |Cite
|
Sign up to set email alerts
|

Body weight prediction using different data mining algorithms in Thalli sheep: A comparative study

Abstract: Background and Aim: The Thalli sheep are the main breed of sheep in Pakistan, and an effective method to predict their body weight (BW) using linear body measurements has not yet been determined. Therefore, this study aims to establish an algorithm with the best predictive capability, among the Chi-square automatic interaction detector (CHAID), exhaustive CHAID, artificial neural network, and classification and regression tree (CART) algorithms, in live BW prediction using selected body measurements in female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The cross-validation was kept at 10, as recommended by Celik and Yilmaz [19]. The following goodness of fit was used to execute the predictive performance of CART, CHAID, and Ex-CHAID [10]. ( )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cross-validation was kept at 10, as recommended by Celik and Yilmaz [19]. The following goodness of fit was used to execute the predictive performance of CART, CHAID, and Ex-CHAID [10]. ( )…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Celik and Yilmaz [19] compared CART, CHAID, and Ex-CHAID and established that CHAID was the ideal algorithm with an R 2 of 71.58% and SD ratio of 0.53 for estimating BW in dogs. Abbas et al [10] compared CART, CHAID, and Ex-CHAID for predicting BW for Thalli sheep and indicated that CHAID was the ideal algorithm with the predicted 64.48% R 2 and 0.59 SD ratio. The CART demonstrated that BL, HG, and wither height play critical roles in BW, inferring it can be chosen to Our records disagree with the findings of Mathapo and Tyasi [11] on Boar goats, and the investigation of Eyduran et al [13] on indigenous Beetal Goat of Pakistan revealed that sex played a crucial role in BW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, K nearest neighbors, decision trees, and random forests were used in Holsteins to predict live body weight (Coşkun et al, 2022). CHAID, exhaustive CHAID, CART, and artificial neural networks were used as predictor algorithms for live body weight in Pakistani Thalli sheep (Abbas et al, 2021). The authors used morphometric measurements in the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The most important reason among for not recording body weight being unavailability of weighing scales. Further, body weights are supplemented with linear body measurements which describe an animal or breed completely than the conventional methods of weighing or grading (Abbas et al, 2021). The linear body measurements of the animals are necessary for establishing breed standards, in judging the quantitative characteristics of meat and helpful in developing suitable selection criteria (Sharaby 1 Sheep Brereding Farm, Balnoi-185 211, Jammu and Kashmir, India.…”
Section: Introductionmentioning
confidence: 99%